It's not the end of the world - Blume, Judy (New York : Dell Laurel-Learf, 2005)
When her parents divorce, a sixth grader struggles to understand that sometimes people are unable to live together
"A Richard Jackson Book."
Keywords: Divorce -- Juvenile fiction